Profitability, Leverage, and CSR: Determinants of Corporate Value in the Food and Beverage Industry on the Indonesia Stock Exchange - Naili Amalia; Rina Wulandari (Universitas Muhammadiyah Sorong, 2026)
This research addresses the ongoing inconsistency in prior empirical findings regarding the role of profitability, leverage, and Corporate Social Responsibility (CSR) in shaping firm value, particularly within the manufacturing sector of emerging markets. Specifically, the study examines the effect of profitability and leverage on firm value, with CSR positioned as a moderating variable in food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period. Adopting a quantitative approach, the research applies multiple linear regression and moderation analysis using secondary data derived from annual and sustainability reports of firms selected through purposive sampling. Firm value is measured using Tobin’s Q, while profitability and leverage are proxied by Return on Assets (ROA) and Debt to Assets Ratio (DAR), respectively. The empirical results reveal that profitability (ROA) does not have a significant impact on firm value, whereas leverage (DAR) demonstrates a positive and significant effect. Moreover, CSR neither exerts a direct influence on firm value nor functions effectively as a moderating variable in the relationship between profitability, leverage, and firm value. The low Adjusted R-squared value of 3.44% indicates that firm value is influenced by a broader set of factors beyond the financial and non-financial variables incorporated in this model, highlighting a gap in existing explanatory frameworks. Theoretically, this study contributes to the literature by providing empirical evidence that challenges the assumed strategic role of CSR as a value-enhancing mechanism in the Indonesian manufacturing context.